Synthesis and characterization of MgAlC03- hydrotalcite / Norfarahnazalizan Bidin - Bidin, Norfarahnazalizan (Faculty of Applied Sciences, 2009)
Hydrotalcite is anionic clay that is found in nature and can be easily synthesized in the laboratory by co-precipitation of dilute solutions of magnesium and aluminium hexa hydrates with sodium carbonate. It is composed of mixed layers of Mg and Al, with interlayer anions, most commonly carbonate, to provide overall charge neutrality. Hydrotalcite is one of a number of clays that preferentially adsorb anions, the class referred to as anion clays. Under co-precipitation method, different molar ratio of hydrotalcite was synthesized and characterized. XRD analyzed showed decrease in intensity and increase in basal spacing. The FTIR showed the functional groups of the hydotalcite. SEM showed the surface particles of the hydrotalcite which was irregular shape. The adsorption ability of hydrotalcite was observed by using the AAS. The ability of the hydrotalcite, towards hydotalcite:Cu> Pb> Cd. While, for the contact time, as the contact time increase, the percentage uptake also increases.